(untitled) (Bangladesh Journal of Botany, 2011)
Pollen morphological structures of eight Turkish species of Ajuga, namely A. bombycina Boiss., A. chamaepitys (L.) Schreber ssp. chia var. chia (Schreber) Arcangeli, A. chamaepitys (L.) Schreber ssp. chia var. ciliata Briq., A. chamaepitys (L.) Schreber ssp. cuneatifolia (Stapf) P. H. Davis, A. genevensis L., A. laxmannii (L.) Benthum, A.orientalis L. and A. reptans L. have been studied under light and scanning electron microscopes for the first time. It is revealed that the pollen grains of Ajuga taxa are more or less suboblata-subprolata and tricolpatae. The exine sculpture is granulate in A. chamaepitys subsp. chia var. chia, A. chamaepitys subsp. cuneatifolia, A. genevensis, A. laxmannii, A. orientalis and A. reptans, but it is reticulate in A. bombycina and A. chamaepitys subsp. chia var. ciliata. Key words: Turkish Ajuga; Pollen morphology; Taxonomic value DOI: http://dx.doi.org/10.3329/bjb.v40i1.7994 Bangladesh J. Bot. 40(1): 29-33, 2011 (June)